Histopathology as a key to identify Sezary syndrome in patient with clinical erythroderma - Sonia Diovani; Irianiwati; Sri Awalia Febriana; Fajar Waskito; Dwinanda Almira Rizkiani; Raden Roro Rini Andayani; Ani Rifko (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Sezary syndrome (SS) is a rare and aggressive variant of cutaneous T-cell lymphoma (CTCL), characterized by clonal proliferation of malignant T lymphocytes with skin erythroderma. The incidence of CTCL in the United States from 2000 to 2010 reached 10 cases per million people per year, accounts for only 3% of all cases of cutaneous lymphoma. In Indonesia, lymphoma ranks sixth in terms of malignancies, alongside Hodgkin lymphoma and leukemia. We reported a case of 56 y.o. woman presented with blistering lesions that turned into wounds all over her body. Skin biopsy examination revealed characteristic histopathological features, including basket weave-type orthokeratosis, focal parakeratosis, focal acanthosis, and epidermotropism of atypical lymphoid cells with cerebriform nuclei (Sezary cells). Immunohistochemical examination using CD3, CD4, and CD8 showed positive staining in the membrane and cytoplasm of tumor cells within the dermis and epidermis. Sezary syndrome is characterized by clonal expansion of T-helper memory cells in the skin. Histopathology and immunohistochemistry could not differentiate SS from mycosis fungoides. However, histopathological examination could distinguish SS from other differential diagnoses. The diagnosis of SS can be established based on the triad of 1) generalized exfoliative dermatitis involving more than 80% of the body surface area, 2) lymphadenopathy, and 3) the presence of 5% or more malignant T-cells with cerebriform nuclei (Sezary or Lutzner cells) in peripheral blood lymphocytes. In conclusion, we present a case of SS, diagnosed based on the patient's history, physical examination, peripheral blood examination, histopathology, and immunohistochemistry.